Cross-Gender Students: Victims of “Rape Prank” - Wiwatwongwana, Rangsima (Scholar: Human Sciences, 2021)
The purpose of this qualitative research is to study the types of bullying in cross-gender students, and a challenge that cross-gender students have to encounter. This research uses Feagin's (1963) and the concept power relations of Michel Foucault empirical influencing of Power on Stigma Theory was used as a framework. Data collection and analysis were performed by using a structured interview protocol. There were five interviewees who identified themselves as cross-gender (Ka-thoeys in Thai). In addition, they were students at a public school in Chiang Mai, Thailand. Non-participant observations were also used to collect the data by observing their social behavior in the school. The results showed that these cross-gender students were bullied in a form of “rape prank” or sexual forcing which embarrassed them in public by their friends and senior students every day. They felt the school was unsafe. Classrooms and restrooms tended to be the location where the cross-gender students were bullied the most. This bullying led to their depression disorder and suicide. This research helps to inform basic information about school regulations. Every schools should announce bully-free regulations and enforce them. Moreover, these regulations should support all genders. Bullies should be sentenced to punishment. In order to eliminate bully and abuse from schools, regulators should enforce the regulations and create a safe environment for students focusing those who identify themselves as cross-gender students.